Cash holdings, leverage, ownership concentration and board independence : evidence from Malaysia / Rahayu Izwani Borhanuddin - Borhanuddin, Rahayu Izwani (2007)
The study aims to investigate the relationship between cash holdings and leverage of Malaysian companies. The main objective of this study is to investigate the relationship between cash holdings and leverage in the context of Malaysian firms. The present study also attempts to compare the cash holdings between companies that having low level of ownership concentration and high level of board independence (good corporate governance) and companies that having high level of ownership concentration and low level of board independence (poor corporate governance). Leverage, cash flow variability, liquidity, growth, size and capital expenditure are used as corporate cash holdings determinants. The final sample of the study consists of 276 companies with 875 observations from six main industries on the Main Board of Bursa Malaysia over a period of four years (2002 to 2005). Linear regression analysis was used to test the relationship between cash holdings and leverage. The results show that there are significant negative relationships between cash holdings and leverage with or without control variables. In addition, this study also found that the companies that have poor corporate governance hold a high level of cash compared to companies that practice good corporate governance. Overall it can be concluded; leverage acts as a substitute of cash holdings and play important part of cash management policies.